Agronomic study of two annual helianthus species naturalized in Argentina as potential sunflower crop genetic resource - Cantamutto, Miguel Angel (Universitat de Lleida, España, 2019)
Tesis para obtener el grado de Doctor, del Departament de Producció Vegetal i Ciència Forestal de la Universitat de Lleida, en 2008